LA INFLUENCIA DE LA POESÍA MACARRÓNICA EN LA POESÍA LATINA HUMANISTA EN ESPAÑA: LA CALLIOPERRIA DE JUAN DE VERGARA - Domínguez Leal, José Miguel (Myrtia, 2002)
This article offers a description of the influence of the macaronic works of Teofilo Folengo (1491-1544) in the latin epic poetry in Spain.